Influence of Strain‐hardening on the Load‐carrying Behaviour of Bearing Type Bolted Connections. Issue 4 (14th September 2022) - Studer, Patrick; Taras, Andreas
Abstract: The investigations presented in this conference paper focus on the hole bearing resistance of symmetric single‐bolt connections, taking into account the distinct hardening behaviour of various steel grades and quantifying its impact on the resulting load‐carrying behaviour. They synthetize the findings of a larger study that was published in full in previous publications by the authors. The main focus of the study was put on the limitation of the hole bearing deformations by defining a corresponding "resistance", which is thus a quantity with the background of an implicit deformation limitation. Experimental investigations were carried out on four different steel grades, each with eight different geometries, in order to investigate the influence of this hardening behaviour on the hole bearing deformations. The paper presents a new approach to define the point on the load‐deformation curve between acceptable and excessive deformations. Based on the results of the hole bearing tests in combination with the new approach to define the transition point between acceptable and excessive deformations, an adapted resistance model is presented. In this model, the hardening behaviour of the steel is taken into account, whereby here specifically the ratio fu /fy of tensile strength to yield strength influences the load‐bearing behaviour. The proposed adaptation of the hole bearing verification which takes the fu /fy ratio into account facilitates the optimal use of material and can thus save resources. The format of the hole bearing verification remains almost unchanged, which should simplify its applicability in practice.